Medication Insurance Policy - a New Insurance Product in the Polish Health Care System - Piechota, Anna (Olsztyn Economic Journal, 2015)
In the Polish healthcare system, medications (including compounded preparations) are wholly or partially paid for from public funds. Subsidising medications which are either central or incidental to treatment (e.g., when patients are unable to work because of an illness) means that medication costs make up a large percentage of total health expenditure and are a drain on the patients' purse. Medication insurance (or drug coverage) policies are a relatively new product and are featured in business insurance portfolios of only a handful of insurance companies offering coverage for medication costs. This article sets out to discuss and analyze available medication coverage policies.